Edukasi Mitigasi Bencana Gempa Bumi Untuk Siswa Kelas 12 IPS 3 Di SMA Negeri 4 Gorontalo Melalui Sosialisasi Dan Simulasi Berlindung Di Bawah Meja - Melo, Ramla Hartini; Niode, Syarifah Fatimah Setiasih; Igirisa, Mohamad Aldo; Dunggio, Iswan (-, 2025)
This community service program was designed to strengthen the preparedness of high school students in responding to earthquake hazards. The activity was implemented with 12th-grade social science students at SMA Negeri 4 Gorontalo through a combination of disaster education and a simple simulation exercise. The program involved several stages, namely preparation, material delivery, hands-on simulation, and evaluation. The findings indicated that students gained a better understanding of the causes and impacts of earthquakes as well as practical skills for self-protection during seismic events. The results further demonstrated that the simulation of taking cover under the desk enhanced the students’ readiness to respond quickly and appropriately in real situations. This initiative highlights the importance of integrating school-based disaster education to foster a culture of disaster awareness from an early age.